2014
DOI: 10.2147/cia.s73814
|View full text |Cite
|
Sign up to set email alerts
|

Serum total prostate-specific antigen values in men with symptomatic prostate enlargement in Nigeria: role in clinical decision-making

Abstract: BackgroundProstatic enlargement is a common cause of bladder outlet obstruction in men in Nigeria. Malignant enlargements must be differentiated from benign enlargements for adequate treatment of each patient. High serum total prostate-specific antigen (tPSA) levels suggest malignancy, but some of the biopsies done due to a serum tPSA value >4 ng/mL would be negative for malignancy because of the low specificity of tPSA for prostate cancer. This study aims to compare the histologic findings of all prostate spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Table 1 reveals a negative correlation between age at initial presentation and iPSA, but this correlation is not significant. Generally in men, there is a significant positive correlation between age and sPSA, 19 , 20 but it seems that among men with prostate adenocarcinoma, this relationship is altered. This is similar to the finding of Yamoah et al 21 in Ghana.…”
Section: Discussionmentioning
confidence: 97%
“…Table 1 reveals a negative correlation between age at initial presentation and iPSA, but this correlation is not significant. Generally in men, there is a significant positive correlation between age and sPSA, 19 , 20 but it seems that among men with prostate adenocarcinoma, this relationship is altered. This is similar to the finding of Yamoah et al 21 in Ghana.…”
Section: Discussionmentioning
confidence: 97%
“…1). Studies were spread across six countries namely Nigeria (seven) [12,13,18,[23][24][25][26], South Africa (two) [27,28], Kenya (one) [29], Senegal (one) [30], Sudan (one) [31], and Tanzania (one) [32]. Of the 13 studies, ten studies reported sensitivity of PSA, specificity of PSA or both (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The diagnostic accuracy of PSA has been reported with conflicts in sub-Saharan Africa. For example, PSA sensitivity and specificity of 96.3% and 18.2% respectively were reported in Nigeria [18], whereas the sensitivity of 53.3% and specificity of 37.1% were recorded in South Africa [19]. The unpredictability of the PSA test's diagnostic accuracy lies at the heart of this argument.…”
Section: Introductionmentioning
confidence: 98%
“…6 PSA is a serine protease produced almost exclusively by epithelial cells of the prostate gland, and the normal total PSA(TPSA) level in cases of BPH is between 0 and 4 ng/ml. 7 Serum PSA is thought to correlate well with prostate volume and it has also been suggested that high PSA levels predict BPH progression. It has been suggested that prostate volume is an important determinant of BPH progression and response to pharmacotherapy, which has become the mainstay of firstline treatment.…”
Section: Introductionmentioning
confidence: 99%